2021
DOI: 10.1093/biolre/ioab013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and manipulation of O-GlcNAcylation in granulosa cells of bovine antral follicles†

Abstract: Glucose is a preferred energy substrate for metabolism by bovine granulosa cells (GCs). O-linked N-acetylglucosaminylation (O-GlcNAcylation), is a product of glucose metabolism that occurs as the hexosamine biosynthesis pathway (HBP) shunts O-GlcNAc sugars to serine and threonine residues of proteins. O-GlcNAcylation through the HBP is considered a nutrient sensing mechanism that regulates many cellular processes. Yet little is known of its importance in GCs. Here, O-GlcNAcylation in GCs and its effects on GC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…In the current study, we observed that altered O-GlcNAc cycling in response to OGT or OGA pharmacological inhibition reduced cell viability, decreased the expression levels of the proliferation-associated genes CDC42 and PCNA , induced apoptosis, and caused the upregulated BAX/BCL-2 mRNA ratio and CASPASE-3 transcripts, which corroborates the findings of a previous study showing that the accumulation of O-GlcNAc in mouse embryonic neural precursor cells induced by treatment with the OGA inhibitor, PUGNAc, activated Caspase-3 activity and severely damaged the cell viability [ 38 ]. However, this is slightly different from a recent study conducted on GCs of bovine antral follicles, which revealed that the manipulation of O-GlcNAc by inhibiting the HBP or via the OGT inhibitor, OSMI-1, impairs GC proliferation, but perturbation of O-GlcNAc via the OGA inhibitor, Thiamet-G, has no obvious effect on GC proliferation [ 24 ]. This discrepancy may be due to the different OGA inhibitor used.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the current study, we observed that altered O-GlcNAc cycling in response to OGT or OGA pharmacological inhibition reduced cell viability, decreased the expression levels of the proliferation-associated genes CDC42 and PCNA , induced apoptosis, and caused the upregulated BAX/BCL-2 mRNA ratio and CASPASE-3 transcripts, which corroborates the findings of a previous study showing that the accumulation of O-GlcNAc in mouse embryonic neural precursor cells induced by treatment with the OGA inhibitor, PUGNAc, activated Caspase-3 activity and severely damaged the cell viability [ 38 ]. However, this is slightly different from a recent study conducted on GCs of bovine antral follicles, which revealed that the manipulation of O-GlcNAc by inhibiting the HBP or via the OGT inhibitor, OSMI-1, impairs GC proliferation, but perturbation of O-GlcNAc via the OGA inhibitor, Thiamet-G, has no obvious effect on GC proliferation [ 24 ]. This discrepancy may be due to the different OGA inhibitor used.…”
Section: Discussioncontrasting
confidence: 78%
“…Glucose is an important metabolic substrate and preferably utilized by GCs to provide the oocytes with energy production [ 23 ]. A recent study demonstrated that O-GlcNAcylation varies in different sizes of antral follicles and influences GC proliferation in bovines [ 24 ]. However, the detailed molecular regulation of O-GlcNAcylation in GC function is just beginning to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…104 The cellular O-GlcNAcylation cycle is believed to be strictly controlled by HBP flow and UDP-GlcNAc concentration. 105 The HBP and UDP-GlcNAc link altered metabolism and O-GlcNAcylation, providing an important mechanism for cells to perceive and respond to nutrient availability. 106 For example, hyperglycaemia causes an increase in intracellular UDP-GlcNAc…”
Section: O-glcnacylation Is Extremely Sensitive To Liver Metabolite N...mentioning
confidence: 99%
“…Also, in sheep, glycolytic metabolism was upregulated in gonadotropin-stimulated antral follicles, as reflected by increased glucose uptake and lactate production 31 . Abigail et al found that GCs of small follicles exhibit enhanced glucose uptake and glycolytic metabolism in bovine 32 . In vitro studies in pigs showed that increased proliferation of GCs in small follicles undergoing development is accompanied by a metabolic shift toward aerobic glycolysis 33 , indicating that the glycolytic pathway is a major player of GCs function in different species.…”
Section: Introductionmentioning
confidence: 99%